Optical Properties of CdS : Au NPs Nanocomposite - V. Kusnezh; A. Danylov; H. Il’chuk; R. Petrus’ (Журнал нано- та електронної фізики)
The CdS : Au NPs nanocomposite film fabrication by combination of CdS thin film chemical deposition and Au NPs growth by annealing of the continuous gold film of 6 and 12 nm thickness was considered. The optical properties of CdS films at every stage of nanocomposite formation were studied. Absorption and transmission spectra of the samples in the visible region were measured; the wavelengths of plasmon resonance and optical band gap were determined.